Policies to Increase Calves Production in East Nusa Tenggara as a National Production Center - Ulrikus Romsen Lole; Arnoldus Keban (ANIMAL PRODUCTION, 2020)
The determinant factors of the growth of calf cattle production in NTT Province (both technical/technological, economic, socio-cultural, investment, and related institutions) have not been specifically identified and measured. This is very important for the purpose of formulating and implementing related policies. The objectives of this study were to analyze the main factors affecting the level of calf production, and to formulate policy interventions to increase calf production. A research survey was carried out on parties related to the planning and development of cattle business. The quantitative approach is in the form of regression analysis of time series data. The economic phenomenon of calf production in Kupang Regency has been simplified into a mathematical model (response function). The result reported that the estimated value of the parameters in the total calf production equation model in NTT was: TPRAS= – 20434.1 + 0.2262 LTTSIP* – 0.0032 TLPRAns + 0.2147 TLLTP* + 0.1036 TPTRU* + 0.1877 TRKUT** + 0.2067TRDIB** + 0.1057 TRDVT** + 0.3647 LTPRAS* + 811.7645 TREND**. In conclusionl, the increased production of calves was dependent on the increase in support for the main production factors [number of productive cows, number of farmers, amount of feed, and amount of cement/vaccine] adequatly. Policy investment (through interest rates and realization farming loans), policy of productive cows control (through postponement of slaughter and the provision cash incentives), and policy of technology support (through realization AI doses of semen and livestock vaccines) significantly affect to production of calves.